"Sensible protesters began leaving the protests": A comparative study of opposing voices in the Hong Kong political movement. (January 2019) - Ho, Janet
Abstract: This corpus-based study investigates the discursive presentations of the main social actors in the media coverage of the Hong Kong Umbrella Movement circa 2014. In particular, this work compares the strategies deployed by the South China Morning Post and China Daily in depicting the involvement of China, the Hong Kong government, the protesters and the students in the incident. The analysis of word co-occurrences revealed that the discursive portrayals of the social actors were very different in the South China Morning Post and China Daily, and a wide range of discursive strategies were used to construct the social actors, including predication, nomination and perspectivization. Highlights: In the SCMP, students were described as determined, innocent and uncontrollable, whereas in China Daily, they were depicted as ignorant and easily controlled. The image of protesters in the SCMP was said to be persistent, whereas their image in China Daily was as violent actors. The Hong Kong government was portrayed in the SCMP as incapable and unresponsive, whereas it was described in China Daily as patient and law-abiding. The SCMP deployed predication and perspectivization through a wide range of linguistic and textual devices. The use of the other newspapers' critiques in China Daily likely served as a strategy for the newspaper to show the 'objectivity' of their stance and their loyalty to the central government.